“¡Viva la revolución y la patria!”. Partido Comunista de Chile y nacionalismo (1921-1926) - Álvarez Vallejos, Rolando (Revista de Historia Social y de las Mentalidades, 2025)
Historical interpretations about the communist parties usually attempt to emphasize international factors and influences to define their political actions. This approach seems to be proved during the Third International, Komintern, since it had critical influence on the communist parties around the world. Without trying to annihilate such significance, this article seeks to demonstrate that within the Chilean Communist party, the nationalistic discourse was fundamental in the way the party organized and developed since the early 1920s. This fact allowed the Chilean Communists to win prestige and support within the popular sectors, those which were prepared to listen and understand a nationalistic rhetoric.